LEGAL CONSEQUENCES OF SELLING ANTIBIOTICS DRUGS WITHOUT DOCTOR’S PRESCRIPTION IN PHARMACIES - Khomsiyah; Zamroni, Mohammad; Adriano (JILPR Journal Indonesia Law and Policy Review, 2024)
The use of antibiotic drugs is subject to statutory regulations, which require a doctor's prescription for purchase. Antibiotic drugs are classified as "list G drugs" or "hard drugs," and they can only be submitted with a doctor's prescription. The objective of this investigation is to examine the legal liability of pharmacies as sellers of antibiotics without a doctor's prescription and the legal repercussions for purchasers of antibiotics without a prescription. This research employs a form of normative legal research. This research employs a normative legal research method that employs primary data sources and secondary data, or data obtained through a statutory and conceptual approach. The results of this study are that the Pharmacist, as a pharmacy supervisor, is fully responsible for the delivery and collection of drugs to prevent unwanted events. Patients will not receive legal protection if they fail to comply with the Pharmacist's instructions to refrain from purchasing antibiotics without a doctor's prescription.